Sosialisasi Digital Marketing untuk Pengembangan Usaha UKM di Kecamatan Purwokerto Selatan Kabupaten Banyumas - Setiyanti, Novita; Wibowo, Raden Mas Arif; Nuha, Ahmad Ulin (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
The transformation of the business landscape driven by the development of digital technology requires Small and Medium Enterprises (SMEs) to adapt their marketing strategies. Digital marketing has become a relevant approach as it enables SMEs to reach consumers more broadly, quickly, and efficiently. This community service activity aims to enhance the capacity of SME actors in South Purwokerto District, Banyumas Regency, to understand and utilize digital marketing as a means of business development. The methods employed include socialization activities, training sessions, and technical assistance related to the use of digital platforms, the formulation of digital marketing strategies, and the development of promotional content aligned with the characteristics of SME products. The results of the activity indicate an improvement in participants’ understanding of the strategic role of digital marketing, as well as increased awareness of the importance of integrating digital technology into their business marketing activities.